PURWARUPA SISTEM KENDALI KETINGGIAN AIR BERBASIS LABVIEW MENGGUAKAN KOMUNIKASI WIRELESS - , DIANITA SAWITRI, R. Sumiharto, S.Si., M.Kom. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Monitoring system has been implemented on LabVIEW-based water level control with eTape sensor. This system works automatically. One of the example is a prototype water level control based LabVIEW with wireless communication. This prototype is designed to simplify the measurement of water level in the tank. The design of this system using a eTape sensor, Arduino, and also relay and mosfet are used as the driving actuators. This system is used to adjust the height in the tank that works to determine the lower limit and upper altitude. When the tank 1 is less than limit, microcontroller on the Arduino will turn on the relay. When the water in the tank reaches a set point, the pump motor will stop working. Every changes in level is read by the sensor and will sent to the Arduino microcontroller then processed and then sent to a computer via wireless communication. On the computer, the data is received then displayed to the chart in \"real time\" and also illustrated with animated elevation changes on the tank and LED. For the next step solenoids work and emptying the tank 1. When do the emptying, the water flows into the tank 2. The results of the testing is system every change in the height shown by the graph in real time, the sensor used work enough. The monitoring system can benefit from knowing the height of the water in the tank without looking directly into the tank.